Isolation, expansion and differentiation of mesenchymal stromal cells from rabbits' bone marrow - Renato B. Eleotério; Rodrigo V. Sepúlveda; Emily C.C. Reis; Fabrício L. Valente; Andréa P.B. Borges (Pesquisa Veterinária Brasileira, 2016)
Abstract: Tissue engineering has been a fundamental technique in the regenerative medicine field, once it permits to build tri-dimensional tissue constructs associating undifferentiated mesenchymal cells (or mesenchymal stromal cells - MSCs) and scaffolds in vitro. Therefore, many studies have been carried out using these cells from different animal species, and rabbits are often used as animal model for in vivo tissue repair studies. However, most of the information available about MSCs harvesting and characterization is about human and murine cells, which brings some doubts to researchers who desire to work with a rabbit model in tissue repair studies based on MSCs. In this context, this study aimed to add and improve the information available in the scientific literature providing a complete technique for isolation, expansion and differentiation of MSCs from rabbits. Bone marrow mononuclear cells (BMMCs) from humerus and femur of rabbits were obtained and to evaluate their proliferation rate, three different culture media were tested, here referred as DMEM-P, DMEM´S and α-MEM. The BMMCs were also cultured in osteogenic, chondrogenic and adipogenic induction media to prove their multipotentiality. It was concluded that the techniques suggested in this study can provide a guideline to harvest and isolate MSCs from bone marrow of rabbits in enough amount to allow their expansion and, based on the laboratory experience where the study was developed, it is also suggested a culture media formulation to provide a better cell proliferation rate with multipotentiality preservation.